The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.4238/gmr.15017625
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian approach increases accuracy when selecting cowpea genotypes with high adaptability and phenotypic stability

Abstract: ABSTRACT. This study aimed to verify that a Bayesian approach could be used for the selection of upright cowpea genotypes with high adaptability and phenotypic stability, and the study also evaluated the efficiency of using informative and minimally informative a priori distributions. Six trials were conducted in randomized blocks, and the grain yield of 17 upright cowpea genotypes was assessed. To represent the minimally informative a priori distributions, a probability distribution with high variance was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…The coefficient of experimental variation (CV e ) was 26.88% (Table 2), which is similar to that found in previous studies on the cowpea (Almeida et al, 2012;Santos et al, 2014a,b;Torres et al, 2015;Barroso et al, 2016). Because it was grain yield this value was expected, since this trait was significantly influenced by the soil and climatic features of each environment (Table 1).…”
Section: Resultssupporting
confidence: 77%
“…The coefficient of experimental variation (CV e ) was 26.88% (Table 2), which is similar to that found in previous studies on the cowpea (Almeida et al, 2012;Santos et al, 2014a,b;Torres et al, 2015;Barroso et al, 2016). Because it was grain yield this value was expected, since this trait was significantly influenced by the soil and climatic features of each environment (Table 1).…”
Section: Resultssupporting
confidence: 77%
“…These results indicated that the use of informative a priori distributions provided more accurate results. Even though the a priori information for each genotype was based on a single study, similar results were found in studies that evaluated the adaptability and phenotypic stability of the dry matter yield of alfalfa genotypes (Nascimento et al, 2011), popcorn grain yield (Couto et al, 2015), and cowpea grain yield (Teodoro et al, 2015;Barroso et al, 2016). Therefore, it is expected that the results will be more precise in studies examining the stability and adaptability of other crops with more available information for meta-analysis.…”
Section: (Equation 25)mentioning
confidence: 53%
“…Several studies have already demonstrated the productive potential of cowpea in the Cerrado-Pantanal ecotone region (Santos et al, 2014b(Santos et al, ,c, 2015Teodoro et al, 2015a,b;Torres et al, 2015aTorres et al, ,b, 2016Barroso et al, 2016).…”
Section: Introductionmentioning
confidence: 99%